The effect of gelatin bloom strength on dry extruded pet food and injection molded treats - Manbeck, Analena (Kansas State University, 2016)
Pet food is a $23 billion industry that continues to grow. Owners continue to humanize their pets and their dietary needs, thus the pet food industry tends to mirror human dietary trends. Currently, pet food is trending towards higher levels of protein, thus lower levels of starch. Decreasing starch, one of the main structure forming ingredients in extruded foods, creates issues in terms of lower rates of expansion and decreased kibble durability. Consumers tend to dislike ingredients that do not serve a dual nutritional purpose; therefore gelatin may be a plausible binding ingredient for high protein pet foods. Gelatin is a pure protein derived from collagen and is sold as a dry, odorless, tasteless powder. High-bloom gelatins find numerous uses in the human food as a stabilizer, foaming agent, and capsule base among other uses. Low-bloom gelatin may find a value-adding opportunity as a nutritional binder in the pet food market. Four extrusion experiments were performed to test this hypothesis. Experiment 1 compared gelatin at 0%, 5%, 10%, and 15% inclusion and 15% gelatin at 3 different extruder screw speeds. Results showed a decrease in expansion but an increase in hardness and pellet durability index (PDI); however there may have been inadequate preconditioning. It was unclear whether the decrease in expansion or presence of gelatin improved product durability. Experiment 2 analyzed two levels of gelatin, 0% and 10%, under two extruder screw speeds, 300 rpm and 500 rpm, and two hydration ratios, 17% and 28%. In this experiment, there were no differences in density, expansion, hardness, or PDI. This indicated that preconditioning was more ideal and may indicate gelatin does not decrease product expansion. Experiment 3 analyzed two levels of gelatin, 0% and 10%, at two target densities, low and high. Results indicated that gelatin created a more expanded product when processed under similar conditions as a control formula. Experiment 4 analyzed different strengths of gelatin to determine if the low-bloom gelatin experiments were repeatable with more conventional strength gelatins. Treatments were a control with no gelatin, and a 100 bloom, 175 bloom, and 250 bloom gelatin. Results showed increased gelatin strength increased product expansion, likely through a foaming effect. However, durability declined with mid- and high-bloom gelatins; thus, low-bloom gelatin may be the most promising to improve product characteristics and preserve durability. Two additional experiments were performed in order to explore gelatin bloom strength in injection molded treat processing. A lab-scale experiment was performed to optimize an initial formula. Tensile strength, strain at break, Young’s Modulus, puncture force, and peaks were measured. It was determined that equal parts gelatin, gluten, and glycerin were most ideal for further testing purposes. Determination of gelatin bloom strength effects with three bloom strength gelatins were used to produce beadlets on a pilot-scale twin-screw extruded and production model injection molding system. Differences were noted between treatments; wherein high bloom gelatin created a softer, more stretchy treat and low bloom gelatin created a tougher, more rubbery treat. Low-bloom gelatin may find use as a nutritional binder in high protein pet foods and may be an alternative to high-bloom gelatin in injection molded dental treats.
Keywords: Pet food; Gelatin; Extrusion; Injection molding; Agriculture, General (0473); Food Science (0359)